Optimasi parameter resistance spot welding pada pengabungan baja electro-galvanized menggunakan metode Taguchi - Sukarman, S.; Abdulah, A. (Universitas Mataram, 2021)
The present study features analytical and experimental results of optimizing resistance spot welding performed using a pneumatic (electrode) force system (PFS). This optimization was carried out to incorporate the galvanized steel sheet material SECC-AF (JIS G 3313) and SPCC-SD (JIS 3141) sheet plate coated with zinc with a thickness of about 2.5 microns. The zinc coating on the metal surface causes its weldability to decrease. This study aims to obtain the highest tensile shear strength test results from the combination of the specified resistance spot welding parameters. The research method used the Taguchi method using four variables and a combination of experimental tingkats. This study's experimental tingkat is two tingkats in the first parameter and three tingkats in other parameters. Taguchi optimization results show that the highest tensile shear strength test obtained is 5049.64 N. This was achieved at 22 cycles of squeeze time, 25 kA of welding current, and 0,6-second welding-time, and 12 cycles of holding-time. The S / N ratio analysis found that the welding time had the most significant effect, followed by welding current, holding time, and squeeze time. The delta S / N ratio values were 0.62, 0,41, 0.34 and 0.07, respectively.